FREKUENSI PEMBERIAN SARI DEDAK PADI TERFERMENTASI SEBAGAI PAKAN TERHADAP PERTUMBUHAN POPULASI Daphnia sp - Dini Desti Natalia; yulisma .; Ade Dwi Sasanti (Universitas Sriwijaya, 2016)
ABSTRACT Daphnia sp. cultivation needs feed to support it’s growth. Rice bran fermented is a likes of material than can be used is feed for Daphnia sp.. The purpose of this research was to know the effect of different frequency of rice bran to population density and population growth of Daphnia sp.. the feed given must be complicated the need of Daphnia sp. as quantitys, quantitative, and feeding frequency. This research was conducted at Laboratorium Dasar Perikanan, Program Study of Aquaculture, Faculty of Agriculture, Sriwijaya University, Indralaya since October until November 2015. This study used randomized completely design method with six treatments and three replications. The treatments were, A: Feeding Frequency ones per day was (07.00 WIB), B: Feeding Frequency twice per day (07.00, 17.00 WIB), C: Feeding Frequency three times per day (07.00, 12.00, 17.00 WIB), D: Feeding Frequency ones per two days (07.00 WIB), E: Feeding Frequency twice per two days (07.00, 17.00 WIB) and F: Feeding Frequency three times per two days (07.00, 12.00, 17.00 WIB). The result indicated that frequency of rice bran fermented using tape yeast twice per day 5 mL.L-1 in once given everyday (treatments B) has the highest of population density and population growth 1,584.33 Ind.L-1 of result density and 39.72%.day.-1 of population growth. Keywords : Daphnia sp., rice bran, feeding frequency, tape yeast